13 bankers : the wall street takeover and the next financial meltdown - Johnson, Simon , 1963-; Kwak, James (Pantheon Books, 2010)
Johnson and Kwak examine not only how Wall Street's ideology, wealth, and political power among policy makers in Washington led to the financial debacle of 2008, but also what the lessons learned portend for the future